Role of Nuclear Non-Canonical Nucleic Acid Structures in Organismal Development and Adaptation to Stress Conditions - Alecki, Célia; Vera, Maria (Frontiers in Genetics, 2022)
Over the last decades, numerous examples have involved nuclear non-coding RNA (ncRNA) in regulating protein-coding gene expression. ncRNA can interact with the genome by forming non-canonical nucleic acid structures such as R-loop or DNA-RNA triplex, which may allow or prevent the targeting of proteins involved in gene expression regulation. These structures can also modify the chromosomal architecture by preventing interaction between two distal parts in the genome. We review the function of these nuclear ncRNAs that have or have not formed non-canonical nucleic acid structures in multicellular eukaryotic organisms during development and in response to different stress conditions and DNA damage. We overview recent technics developed to study ncRNAs and their function and describe examples of R-loop or DNA-RNA triplexes involved in development and the cell stress response.